PENGEMBANGAN MODEL PEMBELAJARAN HYPNOTEACHING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA SMA/MA - Hepta Bungsu Agung Jayawardana; Djukri Djukri (Jurnal Inovasi Pendidikan IPA, 2015)
Penelitian ini bertujuan untuk mengetahui: (1) validitas model pembelajaran hypnoteaching beserta perangkat pembelajarannya; (2) pengaruh model pembelajaran hypnoteaching terhadap peningkatan motivasi belajar siswa; dan (3) pengaruh model pembelajaran hypnoteaching terhadap peningkatan hasil belajar biologi siswa kelas XI SMA/MA. Prosedur pengembangan dalam penelitian ini diadaptasi dari Model Borg Gall yang meliputi studi pendahuluan dan pengumpulan informasi, perencanaan dan perancangan, penyusunan draf model pembelajaran dan validasi, uji coba terbatas dan revisi, uji coba diperluas dan penyempurnaan produk, serta diseminasi dan implementasi produk. Teknik analisis data yang digunakan yaitu statistik deskriptif dan statistik inferensial dengan menggunakan uji multivariat (MANOVA). Hasil penelitian adalah sebagai berikut: (1) Model pembelajaran hypnoteaching beserta perangkatnya, secara empiris valid dan reliabel dengan kategori “Sangat Baik”. (2) Model pembelajaran hypnoteaching mempunyai pengaruh yang signifikan terhadap peningkatan motivasi belajar siswa kelas XI SMAN 2 Banguntapan dan MAN Yogyakarta III, hal ini dibuktikan dengan uji MANOVA dengan nilai signifikansi (Sig.) = 0,000 pada taraf kepercayaan 95%. (3) Model pembelajaran hypnoteaching mempunyai pengaruh yang signifikan terhadap peningkatan hasil belajar siswa kelas XI SMAN 2 Banguntapan dan MAN Yogyakarta III, yang dibuktikan dengan uji MANOVA dengan nilai signifikansi (Sig.) = 0,000 pada taraf kepercayaan 95%. Kata Kunci: model pembelajaran, hypnoteaching, motivasi belajar, hasil belajar kognitif   DEVELOPING OF HYPNOTEACHING LEARNING MODEL TO IMPROVE THE MOTIVATION AND STUDENT'S LEARNING ACHIEVEMENT OF BIOLOGY OF SENIOR HIGH SCHOOL Abstract This research aims to find out: (1) the validity of hypnoteaching learning model including the learning tools; (2) the effect of hypnoteaching learning model for the increasing of student’s learning motivation; and (3) the effect of hypnoteaching learning model for the increasing of student’s learning achievement of biology in 11th grade of senior high school. The procedure development in this reseach was based on the procedural model sequence that was adapted from Borg Gall Model which included preliminary study and collecting of information, planning and designing, drafting of the learning model and validation, limited experiment and revision, extended experiment and product refining, dissemination, and then product implementation. The techniques of data analysis used are descriptive statistics and inferential statistics that used multivariate analysis (MANOVA). The results of this research are: (1) The hypnoteaching learning model with the tools are empiricly valid and reliabel with has  “the best” category. (2) Hypnoteaching learning model have a significant effect for increasing the student’s learning motivation of 11th grade of 2nd Banguntapan Senior High School and Islamic 3nd Senior High School of Yogyakarta, this is evidenced by MANOVA tes that shows the significant level (Sig.) = 0,000 with the confidence level is 95%. (3) Hypnoteaching learning model have a significant effect for the increasing of student’s learning achievement in 11th grade of 2nd Banguntapan Senior High School and Islamic 3nd Senior High School of Yogyakarta, this is evidenced by MANOVA test that shows the significant level (Sig.) = 0,000 with the confidence level is 95%. Keywords: learning model, hypnoteaching, learning motivation, cognitive learning achievement